Knowledge and attitude on folic acid intake among antenatal mothers in preventing birth defects in Hospital Universiti Sains Malaysia - Kamaruddin, Mahirah (2020)
Folic acid intake is one of the concerned issues in the society. Folic acid intake important in preventing birth defects. Folic acid helps the development of the blood cells especially in fetal development. This study aimed to assess the knowledge and attitude on folic acid intake among antenatal mothers in preventing birth defects in Hospital Universiti Sains Malaysia. This was cross-sectional study conducted 160 antenatal mothers who attended Obstetrics and Gynaecology Clinics in Hospital USM. Antenatal mothers who in first trimester were recruited through simple random sampling method. Socio-demographic characteristics, knowledge and attitude among participants were obtained through questionnaire. Data analysis was done using Statistical Package for Social Science (SPSS) version 24.0 software. Results showed that 86.9% of participants had a high knowledge level and 49.2% of them had neutral attitude level on folic acid intake. This study showed no significantly associated between age (p=0.205) and level of education (p=0.813) and knowledge of folic acid intake while there is significantly associated between employment (p=0.001) and knowledge on folic acid intake. This study also showed no significantly associated between age (p=0.452), level of education (p=0.6888) and employment (p=0.256) and attitude on folic acid intake. Hence, programme or activities will be organised to provide more education on folic acid intake in preventing birth defects.